Large Mediastinal Mass Diagnosed After Cardiopulmonary Resuscitation During Cesarean Delivery - Dichtwald, Sara; Avraham, Meyer; Elad, Dana; Nisim, Ifrach; Brian, Fredman (Archives of Clinical and Medical Case Reports, 2021)
Background: Maternal cardiac arrest is rare, with reported incidence of 1:12,000. Ganglioneuroma is a very rare benign tumor, commonly originating in the posterior mediastinum. Here we present a case of cardiac arrest during cesarean delivery, secondary to major vessel compression by a large mediastinal Ganglioneuroma which was unknown before delivery. Case Report: A healthy, nulliparous, 22 year old woman, admitted for urgent cesarean section at 40-weeks gestation under epidural anesthesia due to fetal decelerations and meconium. Shortly after extraction of the fetus, severe hypoxemia and cardiac arrest ensued. Return of spontaneous circulation was accomplished 5 minutes after initiation of cardiopulmonary resuscitation. The patient recovered fully. Imaging revealed large space-occupying lesion of the posterior mediastinum with left lung and pulmonary artery compression with resultant segmental pulmonary embolism. Biopsy did support diagnosis of lymphoma. Left thoracotomy was performed with complete excision of the tumor. Biopsy revealed Ganglioneuroma, and no further therapy was required. Conclusion: To the best of our knowledge, this is the first case report describing maternal cardiac arrest due to undiagnosed large mediastinal Ganglioneuroma. Careful history, along with prompt imaging, tissue biopsy and definitive surgery are necessary to avoid further morbidity and possible mortality.